SAVIME: A Database Management System for Simulation Data Analysis and Visualization - Lustosa, Hermano; Porto, Fábio; Valduriez, Patrick (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2019)
Limitations in current DBMSs prevent their wide adoption in scientific applications. In order to make scientific applications benefit from DBMS support, enabling declarative data analysis and visualization over scientific data, we present an in-memory array DBMS system called SAVIME. In this work we describe the system SAVIME, along with its data model. Our preliminary evaluation shows how SAVIME, by using a simple storage definition language (SDL) can outperform the state-of-the-art array database system, SciDB, during the process of data ingestion. We also show that is possible to use SAVIME as a storage alternative for a numerical solver without affecting its scalability.